2016
DOI: 10.18632/oncotarget.9042
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-199b is associated with distant metastasis in colorectal cancer via activation of SIRT1 and inhibition of CREB/KISS1 signaling

Abstract: The progression of distant metastasis cascade is a multistep and complicated process, frequently leading to a poor prognosis in cancer patients. Recently, growing evidence has indicated that deregulation of microRNAs (miRNAs) contributes to tumorigenesis and tumor progression in colorectal cancer (CRC). In the present study, by comparing the miRNA expression profiles of CRC tissues and corresponding hepatic metastasis tissues, we established the downregulation of miR-199b in CRC metastasis tissues. The decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 43 publications
7
54
0
Order By: Relevance
“…In our present study, we demonstrate that SIRT1 protein directly interactes with CREB protein and deacetylates CREB at the post‐translational level in Lgr5 + GCSCs. CREB deacetylation status led to suppression of the forskolin‐induced CREB phosphorylation, which was in accordance with the conclusions outlined above which also helps to suggest the down‐expression of SIRT1 in Lgr5 + GCSCs.…”
Section: Discussionsupporting
confidence: 90%
“…In our present study, we demonstrate that SIRT1 protein directly interactes with CREB protein and deacetylates CREB at the post‐translational level in Lgr5 + GCSCs. CREB deacetylation status led to suppression of the forskolin‐induced CREB phosphorylation, which was in accordance with the conclusions outlined above which also helps to suggest the down‐expression of SIRT1 in Lgr5 + GCSCs.…”
Section: Discussionsupporting
confidence: 90%
“…MiR‐199b, which is located on chromosome 9q34.11, has been widely researched in recent years and implicated in tumour progression in tumours such as myeloid leukaemia , lymphoid leukaemia , medulloblastoma , choriocarcinoma , endometrioid endometrial carcinoma , ovarian cancer , breast cancer , prostate cancer , hepatocellular carcinoma , colorectal cancer , Kaposi's sarcoma , osteosarcoma and Ewing's sarcoma . Additionally, miR‐199b has also been implicated in other pathologies such as heart failure , idiopathic pulmonary arterial hypertension and intractable epilepsy .…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1) is another protein, which regulates the expression of MMPs and E‐cadherin. Several studies indicated that Sirtuin1 overexpression leads to an upregulation of MMPs and downregulation of E‐cadherin in various cancers, and therefore stimulates cells invasion, metastasis, and EMT …”
Section: Micrornas Epithelial–mesenchymal Transition (Emt) and Oxalmentioning
confidence: 99%
“…In addition, transfection with miR‐199b lentivirus inhibits lung and liver metastasis in CRC nude mice model. The downregulation of miR‐199b predicts a poor prognosis in patients of CRC . These items were presented in Figure .…”
Section: Micrornas Epithelial–mesenchymal Transition (Emt) and Oxalmentioning
confidence: 99%